Menanamkan Konsep Multikulturalisme di Indonesia - Zaenal Abidin (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2016)
Diversity is one of the patterns of social life, and this can not be avoided. Indonesia as a pluralistic country requires a value system that can make this into a unique diversity if managed well, but if not it is a big challenge given will cause a problems such as social conflict, conflict horizontal and national disintegration. Ideology of Pancasila as the nation has not been able to realize a multicultural life, so that the necessary education multiculturalism so that the values contained in Pancasila and "Bhineka Tunggal Ika" can be realized.